Figure of Speech Stylistic Analysis on Selected Song Lyric in GUTS Album by Olivia Rodrigo - Zahara, Ayuna; Hidayat, Chatrine Aulia; Rangkuti, Rahmadsyah (TEKNOSASTIK, 2024)
This study conducts a figure of speech stylistic analysis on selected song lyrics from Olivia Rodrigo's "GUTS" album, "The Grudge," "Lacy," and "Making the Bed." Grounded in the theoretical framework of K.L Knickerbocker and H Willard Reninger (1963), the analysis explores various figures of speech such as metaphor, simile, hyperbole, synecdoche, personification, metonymy, irony, paradox, and allusion. The research aims to unravel Olivia Rodrigo's stylistic choices and determine the most dominant figure of speech used in the selected songs. Data collection techniques in this study are: listen to the songs, read the songs lyric intensively, marking words, clauses, or sentences containing figure of speech proposed by K.L Knickerbocker and H. Willard Reninger (1963) and put it on a table. This study also determines the most dominant figures of speech are found in selected song’s lyrics in "GUTS" album by Olivia Rodrigo. Through a systematic analysis, the findings of this study found 142 figures of speech contained in the selected song lyrics, with hyperbole emerging as the most dominant. The findings highlight Rodrigo's adeptness in using linguistic devices to convey powerful messages and evoke emotions, contributing to a deeper understanding of the artistic and expressive qualities embedded in contemporary music lyrics.